Effect of sources and dosis of phosphorus on the production of maize [Zea mays] and bean (Phaseolus vulgaris) crop system with two methods of tillage - Crissien Escordia, J. (Universidad de Costa Rica, San José (Costa Rica) CATIE, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 1979